The Consequences of Residential Project’s Delay on Architects and Contractors during Pandemic COVID-19 - Norzaki, Sarah Nazihah; Masrom, Md. Asrul Nasid (Research in Management of Technology and Business, 2022)
The study focused on delayed residential projects, which were classified as architects and contractor related issue in the construction industry. In order to assure the client's pleasure and maintained the pandemic issues at the same time, the construction project must be finished within the time restriction of the contract term while also offering the greatest quality possible. The purpose of the study is to study the consequences of delays in the residential project during COVID-19 outbreak, by focusing on the contractors, in Malaysia. Specifically, these was contingent to fulfilling the two objectives, to identify the impact of delay in residential project during pandemic COVID-19 and to investigate the role of the architects and contractors on delay. A qualitative approach was used byinterviewing all the respondents through phone call and video call. The result of the study found that financial issues is one of the worst consequences that they have to face during the pandemic. Based on the survey, contractors are the one who need to bear most of the risk and bad impact during this pandemic